The Effects of Exposure to Air Pollution on Subjective Well-being in China - Xin Zhang; Xi Chen; Xiaobo Zhang (Institute of Labor Economics (IZA), 2019)
This paper studies the impact of six main air pollutants on three key dimensions of subjective well-being (SWB) – life satisfaction, hedonic happiness and mental health. We match a nationally representative survey in China with local air quality and rich weather conditions according to the exact date and county of each interview. By making use of variations in exposures to air pollution across similar respondents living in the same county, we find that PM2.5 reduces hedonic happiness and increases the rate of depressive symptoms, but does not affect life satisfaction. Our results show that the benefits of reducing air pollution would be higher if the hidden costs of air pollution on SWB in China are taken into account.
Keywords: I31; Q51; Q53; 330; life satisfaction; hedonic happiness; depressive symptoms; air pollution; China